2013
DOI: 10.1186/2193-1801-2-359
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and relationship of cattle populations of East India: distinguishing lesser known cattle populations and established breeds based on STR markers

Abstract: India has 34 recognized breeds of cattle in addition to many more not characterized and accredited so far. It is imperative to characterize all the cattle germplasm of the country so as to have better breeding and conservation options. Thus, present study was planned for assessing genetic diversity and relationship between three local cattle populations (Gangatiri, Shahabadi and Purnea) and two established cattle breeds (Bachaur and Siri) of eastern India by using 21 FAO and ISAG recommended microsatellite mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
27
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
9
27
3
Order By: Relevance
“…The current study revealed higher heterozygosity values compared with50-63%, 70%, 71%, 68%, and 70% reported in indigenous cattle from Mozambique (Bessa et al, 2009), South Africa (Sanarana et al, 2016), Senegal (Ndiaye et al, 2015), Cameroon (Ngono-Ema et al, 2014), and India (Sharma et al, 2013), respectively. Higher Ho compared with He and fixation indices suggested that breeds were in HWE.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The current study revealed higher heterozygosity values compared with50-63%, 70%, 71%, 68%, and 70% reported in indigenous cattle from Mozambique (Bessa et al, 2009), South Africa (Sanarana et al, 2016), Senegal (Ndiaye et al, 2015), Cameroon (Ngono-Ema et al, 2014), and India (Sharma et al, 2013), respectively. Higher Ho compared with He and fixation indices suggested that breeds were in HWE.…”
Section: Discussionmentioning
confidence: 86%
“…Edea et al (2013) and Zerabruk et al (2012) reported very low levels of differentiation among Ethiopian cattle populations (F ST = 1% and 1.1%) using single nucleotide polymorphisms (SNPs) and microsatellites, respectively. However, higher F ST values of 13.3% were reported for Indian cattle breeds (Sharma et al, 2013). The moderate value of genetic differentiation may be attributed to recent divergence of the breeds from a common ancestry, reproductive isolation, or moderate selection pressure in the populations from which samples were collected (Felius et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations